2019
DOI: 10.1175/jcli-d-18-0664.1
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Synoptic-Scale Rossby Wave Patterns and Their Effect on the Persistence of Cold and Hot Spells

Abstract: The persistence of surface weather during several recent high-impact weather events has been pivotal in generating their societal impact. Here we examine Hovmöller diagrams of the 250-hPa meridional wind during several periods with particularly persistent surface weather and find a common pattern in these Hovmöller diagrams. This pattern can be characterized as a “recurrent Rossby wave pattern” (RRWP), arising from multiple transient synoptic-scale wave packets. During such RRWP periods, individual troughs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
114
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(118 citation statements)
references
References 64 publications
4
114
0
Order By: Relevance
“…These regions can thus be considered as hot spots for long‐lasting compound hot and dry spells associated with blocking. Interestingly, western North America and central Europe are also areas where recurrent Rossby wave patterns (RRWPs) foster particularly long‐lasting summer hot spells (Röthlisberger et al, ). These areas might thus be particularly prone to persistent heat induced by both blocks and RRWPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These regions can thus be considered as hot spots for long‐lasting compound hot and dry spells associated with blocking. Interestingly, western North America and central Europe are also areas where recurrent Rossby wave patterns (RRWPs) foster particularly long‐lasting summer hot spells (Röthlisberger et al, ). These areas might thus be particularly prone to persistent heat induced by both blocks and RRWPs.…”
Section: Discussionmentioning
confidence: 99%
“…However, also synoptic to hemispheric-scale atmospheric circulation patterns play a pivotal role in generating long-lasting heat waves and droughts. Recent studies have therefore investigated the atmospheric dynamics mechanisms leading to persistent hot surface weather for several recent examples of extremely long-lasting heat waves (Barriopedro et al, 2011;Black et al, 2004;Dole et al, 2011;Fink et al, 2004;Parker et al, 2014;Schneidereit et al, 2012;Xu et al, 2019;Zschenderlein et al, 2018) as well as from a climatological point of view (Kornhuber et al, 2017;Röthlisberger et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(2018) showed that in southern Europe narrow subtropical ridges rather than blocking lead to extremely warm conditions. Rossby‐wave packets (Fragkoulidis et al ., 2018), recurrent (Röthlisberger et al ., 2019) or stationary (Kornhuber et al ., 2019) Rossby waves have also been linked to high temperature extremes. Further, Drouard and Woollings (2018) revealed a regional dependence of the formation and maintenance mechanisms of blocking and their connection to the North Atlantic storm track.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, RWPs organize the formation, intensification, and movement of weather systems and special attention has been given to RWPs as precursors to extreme weather events (e.g., Shapiro and Thorpe, 2004;Martius et al, 2008;Wirth and Eichhorn, 2014;Piaget et al, 2015;Grazzini et al, 2020). Beyond individual weather systems, the recurrent occurrence of RWPs has been associated with periods of temperature extremes (Röthlisberger et al, 2019). And from a climatological perspective, the dynamics of midlatitude storm tracks can be described in terms of the excitation, propagation, and decay of RWPs (Chang and Orlanski, 1993;Chang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%